A breast cancer risk haplotype in the caspase-8 gene - Shephard, Neil Duncan; Abo, Ryan; Rigas, Sushila Harkisandas; Frank, Bernd; Lin, Wei-Yu; Brock, Ian Wallace; Shippen, Adam; Balasubramanian, Sabapathy Prakash; Reed, Malcolm Walter Ronald; Bartram, Claus Rainer; Meindl, Alfons; Schmutzler, Rita Katharina; et al. (Cancer research, 2009)
Recent large-scale studies have been successful in identifying common, low-penetrance variants associated with common cancers. One such variant in the caspase-8 (CASP8) gene, D302H (rs1045485), has been confirmed to be associated with breast cancer risk, although the functional effect of this polymorphism (if any) is not yet clear. In order to further map the CASP8 gene with respect to breast cancer susceptibility, we performed extensive haplotype analyses using single nucleotide polymorphisms (SNP) chosen to tag all common variations in the gene (tSNP). We used a staged study design based on 3,200 breast cancer and 3,324 control subjects from the United Kingdom, Utah, and Germany. Using a haplotype-mining algorithm in the UK cohort, we identified a four-SNP haplotype that was significantly associated with breast cancer and that was superior to any other single or multi-locus combination (P=8.0 x 10(-5)), with a per allele odds ratio and 95% confidence interval of 1.30 (1.12-1.49). The result remained significant after adjustment for the multiple testing inherent in mining techniques (false discovery rate, q=0.044). As expected, this haplotype includes the D302H locus. Multicenter analyses on a subset of the tSNPs yielded consistent results. This risk haplotype is likely to carry one or more underlying breast cancer susceptibility alleles, making it an excellent candidate for resequencing in homozygous individuals. An understanding of the mode of action of these alleles will aid risk assessment and may lead to the identification of novel treatment targets in breast cancer.